Glycemic Status of A Medical Camp Attendees: A Real-world Assessment from Bangladesh - Hasan, Mashfiqul; Atiqur Rahman, Mohammad; Shil, Kishore Kumar; Ratul, Rifat Hossain; Sultana, Nusrat; Hasanat, Muhammad Abul (Bangladesh Journal of Medicine, 2026)
Background: The prevalence of diabetes mellitus (DM) is rising in both rural and urban Bangladesh. Community engagement and motivation in a real-world setting are essential for accurately assessing the true glycemic situation. The aim of the study is to assess the frequency of dysglycemia in people attending medical camps arranged in community level of Bangladesh in a real-world setting. Methods: This survey encompassed 2209 participants(median age 45, interquartile range 36-55 years; female 53.4%; known diabetes 33%)attending medical camps arranged as part of community health awareness programs in urban and ruralareas between2012 and 2024. Capillary blood glucose (CBG) was measured by a calibrated glucometer regardless of feeding or glycemic status. Non-diabetic participants were categorized according to their fasting/random CBG values using oral glucose tolerance test cutoffs, while glycemic control of people with diabetes was considered good add irrespective of affecting factors if fasting CBG<7 or random <10 mmol/L. Results: Among the 1482 participants with unknown glycemic status, 33.4% had capillary blood glucose (CBG) levels indicative of dysglycemia, including DM at 8.4% and prediabetes at 25.0%. The prevalence of dysglycemia, based on fasting CBG (n=1176), was 34.6%, with DM in 8.2% and impaired fasting glycemia (IFG) in 26.4%. Using random CBG (n=306), dysglycemia was found in 18.3%, with DM in 5.6% and impaired glucose tolerance (IGT) in 12.7%. Dysglycemia rates did not differ significantly between genders (p=0.260)but were higher in those aged over 30 years (p=0.012) and those with a family history of DM (p=0.040). Among participants with known diabetes (n=727), only 40% had good glycemic control. Conclusion: One in three newly tested individuals had dysglycemia, while three out of five individuals with known diabetes had poor glycemic control. Bangladesh J Medicine 2026; 37(1): 34-40